Biochemical and Endocrine Parameters for the Discrimination and Calibration of Bipolar Disorder or Major Depressive Disorder - Zhu, Yuncheng; Ji, Haifeng; Niu, Zhiang; Liu, Hongmei; Wu, Xiaohui; Yang, Lu; Wang, Zuowei; Chen, Jun; Fang, Yiru (Frontiers in Psychiatry, 2022)
Objectives: Conventional biochemical indexes may have predictive values in clinical identification between bipolar disorder (BD) and major depressive disorder (MDD). Methods: This study included 2470 (BD/MDD=1333/1137) hospitalized patients in Shanghai as training sets and 2143 (BD/MDD=955/1188) in Hangzhou as test sets. Thirty-five clinical biochemical indexes were tested, including blood cells, immuno-inflammatory factors, liver enzymes, glycemic and lipid parameters, and thyroid and gonadal hormones. A stepwise analysis of a multivariable logistic regression was performed to build a predictive model to identify BD and MDD. Results: Most of these biochemical indexes showed significant differences between BD and MDD groups, such as white blood cell (WBC) in the hematopoietic system, uric acid (UA) in immuno-inflammatory factors, direct bilirubin (DBIL) in liver function, lactic dehydrogenase (LDH) in enzymes, and fasting blood glucose (FBG) and low-density lipoprotein (LDL) in glucolipid metabolism (p’s<.05). With these predictors for discrimination, we observed the area under the curve (AUC) of the predictive model to distinguish between BD and MDD to be .772 among men and .793 among women, with a largest AUC of .848 in the luteal phase of women. The χ2 values of internal and external validation for male and female data sets were 2.651/10.264 and 10.873/6.822 (p’s<.05), respectively. The AUCs of the test sets were .696 for male and.707 for female. Conclusions: Discrimination and calibration was satisfactory, with fair to good diagnostic accuracy and external calibration capability in the final prediction models. Female patients may have a higher differentiability with a conventional biochemical index than males.